Extending shelf-life of peach and pear by using CMC from sugar beet pulp cellulose as a hydrophilic polymer in emulsions - Togrul, H; Arslan, N (Elsevier Sci Ltd, 2004)
Peach and pear were treated with different compositions of emulsions to extend shelf-life of fruits and to preserve the fruit quality. Paraffin wax, beeswax and soybean oil; carboxymethyl cellulose (CMC) with degree of substitution of 0.6670; Emulgin PE, triethanolamine, oleic acid and sodium oleate were used as hydrophobic phases, hydrophilic polymer and emulsifying agents in the coatings of peach and pear, respectively. The CMC obtained by etherification of the sugar beet pulp cellulose was used as a hydrophilic polymer. To investigate the post-harvest water loss of peach and pear, fruits were observed during storage while being subjected to dehydrating conditions in storage chamber at 25 degreesC and 75% relative humidity level. The changes in weight, pH, soluble solids, titratable acidity and ascorbic acid of the coated samples with storage time were measured at regular intervals throughout the storage period to evaluate the effect of storage period on fruit quality. The modified drying models describing the storage time dependence of weight loss were fitted to the experimental data and the model parameters in equations were determined by multiple regression analysis. Some of the coatings decreased the soluble solids, titratable acidity and ascorbic acid losses in comparison to the uncoated peaches and pears. The coating of peach and pear surfaces with emulsions containing CMC from sugar beet pulp cellulose as a hydrophilic polymer extended the shelf-lives of peach and pear to 12 and 16 days, respectively. It was found that a combination using beeswax as hydrophobic phase, triethanolamine and oleic acid as emulsifying agent, CMC as hydrophilic polymer and the emulsion containing soybean oil as hydrophobic phase, sodium oleate as emulsifying agent, CMC as hydrophilic polymers were suitable for the coating of peaches and pears, respectively. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: sugar beet pulp; cellulose; carboxymethyl cellulose; coating; peach; pear